Long-term performance of novel high-calcium one-part alkali-activated cement developed from thermally activated lime kiln dust. (November 2020) - Kadhim, Abdullah; Sadique, Monower; Al-Mufti, Rafal; Hashim, Khalid
Abstract: The traditional activation approach for alkali-activated cement AAC has several problems resulting mainly from the hazardous and corrosiveness of the alkaline chemicals, such as (NaOH, Na2 SiO3 ), which in turn impede the utilisation of AAC in the construction fields. In this study, A second generation of alkali activated binder was developed using Metakaolin (MK) and natural pozzolan material (NP) (as a source of alumina-silicate), these materials were activated using high-calcium lime kiln dust as solid activator to transform the alumina-silicate crystalline phases to cementitious hydrated products. This was achieved with the aid of heat treatment of materials at different temperatures. Raw materials and final AAC samples were characterised using analytical methods, such X-Ray powder diffraction (XRD), Thermogravimetric Analysis (TG-DTA), Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscope (SEM). Additionally, long-term compressive strength, chemical and microstructural performance were investigated. The transformation of raw materials from crystalline to amorphous phases happened due to the effect of the heat treatment and the formation of stratlingite products in the final AAC paste, which were evidenced using the mentioned characterisation methods. The findings of the present study proved that the compressive strength of the new binder reached 27 MPa and 51 MPa after 28 and 180 days of curing, respectively, ensuring a progressive as well as a higher degree of alkali-activation and disappearance of unreacted alkaline substances in the final AAC products. Highlights: One-part earth alkaline activated dry cementitious mixture was produced using thermally activated lime kiln dust (LKD). The presence of LKD and metakaolin in the ternary blend and thermal activation of LKD has provided higher activation rate. 51 MPa compressive strength has generated at 180 days of 950°C calcined LKD and metakaolin in the blend. Considerable changes in mineralogy and amorphicity were evidently accredited to thermal treatment.